2021
DOI: 10.1101/2021.01.11.21249148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prioritizing the Role of Major Lipoproteins and Subfractions as Risk Factors for Peripheral Artery Disease

Abstract: BackgroundCirculating lipid and lipoprotein levels have consistently been identified as risk factors for atherosclerotic cardiovascular disease (ASCVD), largely on the basis of studies focused on coronary artery disease (CAD). The relative contributions of specific lipoproteins to risk of peripheral artery disease (PAD) have not been well-defined. Here, we leveraged large scale genetic association data to identify genetic proxies for circulating lipoprotein-related traits, and employed Mendelian randomization … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…13,14 Similarly, hydrolysis of triglycerides (which are more abundant on VLDL particles) liberates free fatty acids, which may lead to increased inflammation, predisposing to atherogenesis and lesion instability that results in myocardial infarction. Observational and mendelian randomization studies have suggested that atherogenic lipoproteins may not uniformly influence atherosclerotic risk across vascular beds 15,16 and that triglycerides but not LDL-C are associated with markers of systemic inflammation. 17 Future mechanistic studies will be required to characterize the specific interactions between lipoproteins and the arterial wall that may contribute to these differences.…”
Section: See Accompanying Article On Page 2063mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Similarly, hydrolysis of triglycerides (which are more abundant on VLDL particles) liberates free fatty acids, which may lead to increased inflammation, predisposing to atherogenesis and lesion instability that results in myocardial infarction. Observational and mendelian randomization studies have suggested that atherogenic lipoproteins may not uniformly influence atherosclerotic risk across vascular beds 15,16 and that triglycerides but not LDL-C are associated with markers of systemic inflammation. 17 Future mechanistic studies will be required to characterize the specific interactions between lipoproteins and the arterial wall that may contribute to these differences.…”
Section: See Accompanying Article On Page 2063mentioning
confidence: 99%
“…[18][19][20] CGPS participants were also nonfasting, which may have influenced the assessed lipoprotein profile. Although it is likely that VLDL and triglyceride-rich particles represent causal effectors (rather than merely biomarkers) of increased cardiovascular risk based on genetic epidemiology, mendelian randomization, and clinical trial data of triglyceride-lowering therapies, 7,16,[21][22][23] future randomized trials will be required to definitively establish the therapeutic potential of targeting these subfractions. More broadly, these results are consistent with mendelian randomization studies which have prioritized apoB as the causal lipoprotein risk factor for atherosclerosis, 6,16,24 but future studies will be needed to delineate the causal roles of the specific components of each lipoprotein fraction and subfraction.…”
Section: See Accompanying Article On Page 2063mentioning
confidence: 99%